2015
DOI: 10.5812/jjm.8(4)2015.18102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Vibrio cholerae Isolated From Clinical Samples in Kurdistan Province, Iran

Abstract: Background:Aminoglycosides are a group of antibiotics that have been widely used in the treatment of life-threatening infections of Gram-negative bacteria.Objectives:This study aimed to evaluate the frequency of aminoglycoside resistance genes in Enterococcus and Salmonella strains isolated from clinical samples by PCR.Materials and Methods:In this study, 140 and 79 isolates of Enterococcus and Salmonella were collected, respectively. After phenotypic biochemical confirmation, 117 and 77 isolates were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…cholerae is usually used PCR method with specific target genes that act as a virulence factor (Huq et al, 2012;Waturangi et al, 2013;Ramazanzadeh et al, 2015). In addition, the PCR method is a more sensitive and specific molecular laboratory test, fast and accurate when compared to conventional methods (Angeliya and Kurdiwa, 2013;Kharirie, 2013).…”
Section: Oceana Biomedicina Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…cholerae is usually used PCR method with specific target genes that act as a virulence factor (Huq et al, 2012;Waturangi et al, 2013;Ramazanzadeh et al, 2015). In addition, the PCR method is a more sensitive and specific molecular laboratory test, fast and accurate when compared to conventional methods (Angeliya and Kurdiwa, 2013;Kharirie, 2013).…”
Section: Oceana Biomedicina Journalmentioning
confidence: 99%
“…The expression of the virulence genes is a factor that contributes to the pathogenicity of V. cholerae. Some virulence factors present in V. cholera are ToxR regulator, cholerae toxin (consisting of ctxA and ctxB), toxin-coregulated pilus subunit (TcpA), outer membrane protein U (ompU), outer membrane protein W (ompW), accessory cholerae enterotoxin (Ace), and zonula occludens toxin (Zot) (Waturangi et al, 2013;Ramazanzadeh et al, 2015). Cholerae toxin is responsible for the occurrence of diarrhea in cholera outbreaks (Sikora, 2013, Pal, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of nosocomial multidrug-resistant Gram-negative bacteria has caused severe therapeutic problems. Various drug resistance genes such as aminoglycoside, sulfonamide, beta-lactamase and carbapene- mase genes have been studied in Gram-negative bacteria such as K. pneumoniae in Iran and other countries of the world (13)(14)(15)(16)(17). The highest antibiotic resistance rate in the present study belonged to ceftazidime whereas the lowest rate was observed for tobramycin.…”
Section: Discussionmentioning
confidence: 58%
“…The expression of the virulence genes is a major factor contributing to the pathogenicity of V. cholerae. Some of the virulence factors of V. cholerae include ToxR regulator, cholerae toxin (ctxA and ctxB), toxin-coregulated pilus subunit (TcpA), outer membrane protein U (ompU), outer membrane protein W (ompW), accessory cholerae enterotoxin (Ace), and zonular occludens toxin (Zot) (Reidl and Klose, 2002;Waturangi et al, 2013;Ramazanzadeh et al, 2015). The expression of V. cholerae virulence factor is controlled by ToxR regulatory cascade which depends on environmental conditions ( Figure 2) (Raskin et al, 2004;Schild et al, 2008).…”
Section: Expression and Secretion Of Cholerae Toxinmentioning
confidence: 99%